Microbiological profile of ventilator-associated pneumonia among intensive care unit patients in tertiary Egyptian hospitals - Alaa M Farag; Mahmoud M Tawfick; Mostafa Y Abozeed; Emad A Shaban; Maha A Abo-Shadi (Journal of Infection in Developing Countries)
Introduction: Ventilator-associated pneumonia (VAP) is one of the common serious infectious diseases encountered in the intensive care unit (ICU), which highly affects the healthcare cost and patient prognosis. VAP is caused by various antimicrobial-resistant aetiological agents and the clinical manifestations lack sensitivity and specificity, making the prompt treatment is a challenge. This study aimed to investigate the microbial profile of VAP causing microorganisms among ICU patients in Egypt, antimicrobial susceptibility patterns and the genetic diversity among the frequently isolated organisms.